The Development of Student Worksheets Based Problem Based Learning on Amine Topics for 3rd Grade of Senior High School - Oki Marlina Petri; Suryelita Suryelita (Universitas Negeri Padang, 2022)
The Amine is closely related to everyday life, especially the caracteristic and sampling. This subject is a part of the carbon compounds taught on the second semester of 3rd grade High School. But the implementation was transferred to first semester due to the student’s final exam, so the learning process was uneffective.Therefore it needs 2013’s curriculum compatible teaching materials as amine students woeksheet which help students study independently. The purposes of this research are to develop a Problem Based Learning Student Worksheet and determine its validity. The research implementation uses the R&D method. The development stage uses a 4D model consisting of define, design, develop and disseminate which is limited to development due to time and cost limitationsThe data collection technique was carried out by distributing questionnaires. The research data by five expert validators were analysed using the Aiken’s V formula. Based on the a research data obtained the resulting a validity of 0,87 with a valid category.